Acculturative challenges among Pakistani secondary school students in Hong Kong. (May 2021) - Karim, Shahid; Hue, Ming Tak; Ullah, Rizwan
Abstract: Scholars have extensively studied acculturation from different theoretical perspectives among immigrants across the societies of settlement. However, there is a dearth of knowledge about acculturation from a culture learning approach in Hong Kong. This article reports the acculturative challenges among sixteen (16) Pakistani students from six different secondary schools in Hong Kong. The phenomenographic data analysis of semi-structured interviews revealed four categories of everyday experiences in schools that hinder their acculturation. These are mainly related to inter-ethnic interactions, sensitivity towards diverse learning and sociocultural needs, and the Chinese language teaching curriculum for non-Chinese speaking students. Although the study reports Pakistani students' experiences, the findings may also translate the acculturative challenges among students with an immigrant or ethnic minority background in settlement societies. The article also discusses both the theoretical and practical implications for studying and helping immigrant young people in multicultural contexts.